Dermatofibrosarcoma Protuberans of the Breast in Man: An Extremely Rare Entity With a Review of the Literature - Bouhani, Malek (J Investig Med High Impact Case Rep, 2019)
Dermatofibrosarcoma protuberans (DFSP) is a rare sarcoma of soft tissue representing about 1% of all tumors. In addition, DFSP occurs commonly on the trunk and extremities, and only a few cases of DFSP have been observed on the breast. In men, only 11 cases, including this case, have been reported. In this article, we present a case of left breast DFSP that occurred in a 44-year-old man. The physical examination revealed a left breast tender mass, which invaded the skin. The tumor was staged as T4b N0 M0. Mammography and sonography showed a suspect mass of the left breast. The biopsy and immunochemistry permitted the diagnosis of DFSP of the left breast. The patient had a left mammectomy, with free margins. He presents no evident sign of recurrence 7 months later.